Pengembangan Perangkat Pembelajaran Kooperatif Multilevel Pada Pelajaran Matematika di Sekolah Dasar - Atiaturrahmaniah Atiaturrahmaniah (Universitas Islam Negeri (UIN) Mataram, 2014)
This study aims to develop multilevel cooperative teaching kits for Mathematics in Elementary Schools. The kits have been tested and are feasible to use in the learning process. The development of the kits was made through the steps of data collection, product design, product validation, tryouts and revision, and final product. This study produces multilevel cooperative teaching kits for the topic of Fractions, and the kits consist of Lesson Plans, Teacher’s Book, Student’s Book, Student’s Worksheet, and Achievement Test. The results of the study show that the multilevel cooperative teaching kits are in the good category. The scores of the pretest and posttest show that the application of this learning model has a good impact on the students’ learning mastery. Of 82 students, there are 43 students achieving the minimum standard for mastery learning, namely a score of ≥ 65. Meanwhile, the percentage of the learning mastery by using the teaching kits and applying the multilevel cooperative learning strategy is 86.6% or 71 students attaining the mastery, which is in the very good learning mastery category.